Stage of lactation profile reflects nutrition and management - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1994)
The Stage of Lactation Profile (SOLP) is a good estimate of the shape of the lactation curve for dairy herds. The SOLPs for herds with various milk production levels are somewhat similar. The rates of decline of all SOLPs are about the same. Therefore, the differences in production levels are about the same in late stages of lactation and in early lactation, regardless of production Rolling Herd Average (RHA). In addition, higherproducing herds have their highest level of production in the second stage of lactation (51 to 100 days in milk), whereas this occurs in the first stage of lactation (milk) in lower-producing herds. Nutrition and management programs have a large impact on the early stages of lactation that affects the total lactation milk yield.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Stage of lactation; Profile; Summit milk yield; Rolling herd average